Molecular analyses of confiscated shark fins reveal shortcomings of CITES implementations in Germany. Issue 6 (9th March 2021) - Villate‐Moreno, Melany; Pollerspöck, Jürgen; Kremer‐Obrock, Friederike; Straube, Nicolas
Abstract: A three‐ton shipment of dry shark fins was examined by German customs in 2017 leading to the confiscation of 405 kg of potential CITES species. We analyzed a subsample of this material (115 specimens) using DNA sequence‐based identification and compared results to morphological screening of CITES species. We found a mixture of CITES regulated (4 of 11 species) and unregulated shark species. Our results demonstrate the difficulties of identifying CITES species morphologically in large fin shipments of mixed species composition. Correct identification of CITES species based on morphology alone may be hindered by missing characters or those altered by drying. We therefore suggest random molecular screening as a uniform approach for German customs authorities to check species composition and identify CITES regulated species in transit shipments. Abstract : The shark fin trade often relies on transportation routes and transit countries. Precise identification of CITES species based on morphological characters when handling very large shipments could be challenging. We suggest random molecular screening by customs authorities as a uniform approach for checking species composition of in‐transit shipments.